Hadith Study Methods In Modern Pesantren Tuhfatul Athfal Subang District - Hidayatullah, Nurul; Hartati, Hartati; Iskandar, Amin; Anam, Khoirul (Al-Bukhari : Jurnal Ilmu Hadis, 2023)
This article is about "Hadith Studies in Tuhfatul Athfal (Yafata) Modern Islamic Boarding School, Kalijati District, Subang Regency". The problem of Hadith Studies in the Islamic Boarding School environment is familiar in Indonesia because Hadith studies have been entered since the 17th century (Aceh). What distinguishes the theme of the study of the era lies in the scientific area. Hadith material used to include in the fields of fiqh and Sufism in contrast to today which has focused on hadith science (study of hadith books, ma'anil hadith and living hadith). One of the Islamic boarding schools that provides hadith studies is the Tuhfatul Athfal (Yafata) Islamic Boarding School. This Islamic boarding school is the only Islamic boarding school that conducts study activities for its alumni from three sub-districts in Subang regency (Kalijati, Cipeundeuy and Dauan). Based on these problems, the following formulation of the problem was determined "how is the study of Hadith in the modern Islamic Boarding School Tuhfatul Athfal (Yafata) and how effective the methods used for the students are". Meanwhile, to answer the questions that have been set, qualitative research methods are used, with the form of field research field research. The data collection technique is through observation, unstructured interviews and documentation. The results show that this pesantren provides a study of the hadith of the book Riyadh al-salihin. The process begins with tawasul then the teacher translates in terms of meaning and explains its meaning, in his explanation narsum adds Sundanese admonitions and interspersed with jokes, it is intended to make it easier for students to remember the explanation and the study ends with the reading of Alhamdulillah, in this study the method used is bandongan and one-way lectur